Atypical Site of Presentation of a Rare Type of SMARCA4-Positive Cutaneous Squamous Cell Carcinoma of the Skin: Case Report and Review of the Literature - Ruchi Yadav MD; Shaun Din MD; Harry Moussaris MD; Vivek Yadav MD; Shakthi Raman BSc; Anjula Gandhi MD; Boris Avezbakiyev MD; J. C. Wang MD (SAGE Publishing, 2024)
Cutaneous squamous cell carcinoma (cSCC) comprises 20% of cases of nonmelanoma skin cancers in the United States. In total, 3% to 5% of squamous cell carcinoma (SCC) are metastatic at the time of presentation, associated with significant mortality due to a lack of standardized treatment options. In total, 95% of these tumors are amenable to the initial standard of treatment, which is surgical resection. However, a small percentage of them require systemic therapy as they are either locally advanced to regional lymph nodes or have distant metastasis. The common sites of presentation of cSCC are the scalp and the face with predictable spread to the intra-parotid, upper jugular, and perifacial lymph nodes. In our case report, however, our patient had a large lump lesion on the upper back, an unusual site of presentation of cSCC, with locally advanced metastasis to the left axillary lymph nodes. Subsequently, the tumor marker study revealed a positive SMARCA4 variant (the essential ATPase subunit of the Switch (SWI)/Sucrose Nonfermenting (SNF) chromatin-remodeling complex) that is even rarer in the context of cSCC. Furthermore, abnormalities in SWI/SNF chromatin-remodeling complex subunits have shown promising results as a target therapy for immune checkpoint inhibitor (ICI) therapy. We present an atypical presentation site of locally advanced rare variant SMARCA4-positive cSCC in a patient who received treatment with chemoradiation and systemic therapy with ICI after primary surgical resection. To date, only 2 cases of SMARCA4-positive cSCC were found in the literature with no details of the treatment received. Our case is unique in its atypical site of presentation as well as showing partial response to radiotherapy (RT) and systemic therapy with ICI.